Application of the homeostastic approach to the formation of the portfolio of regional development projects - Oberemok, Ivan; Oberemok, Nataliia (Technology audit and production reserves, 2017)
The transition to the knowledge economy requires a change in approach to the management of the development of both: individual regions and entire countries. The definition of competitiveness has become one of the key definitions in the formation of the regional development strategy. For manage the development of the region is recommended to use a project-based approach. At this, the important processes are the processes of formation of a portfolio of projects and determination of their priorities. The peculiarity of regional development projects is that they are aimed at satisfying a large number of different stakeholder groups. Each stakeholder group has its own view of the results of development projects. Providing homeostasis between the stakeholders of regional development projects is a hard job. Because projects demand are formed based on quality indicators. Constantly changing list of quantitative indicators is used to describe the quality indicators. In addition, the indicators themselves change their planned value and their importance in the framework of a quality indicator. Considering limited budget of regional development it is necessary to form a portfolio of projects that will ensure maximum stakeholder requirements. In this regard, the tools of formation and prioritize of regional development projects are proposed to build on the basis of a homeostatic approach. This approach allows to build a complex management system aimed at the survival of the object of manage in an aggressive environment. Realizing the selected projects on the proposed approach, the regional authorities will be able to improve the competitiveness of the region significantly.